Characterization of four novel molecular changes in the promoter region of the factor VIII gene. (30th December 2013) - Nougier, C.; Roualdes, O.; Fretigny, M.; d'Oiron, R.; Costa, C.; Negrier, C.; Vinciguerra, C.
Summary Haemophilia A (HA) is an X‐linked recessive bleeding disorder, caused by a wide variety of mutations in the factor VIII (F8) gene, leading to deficiency in the activity of coagulation FVIII. These mutations can affect all the F8 exons from the initiation codon to the termination codon, however, only few molecular changes in the promoter region of the F8 gene were reported so far. Here, we describe six nucleotide variations (c.‐51G>A, c.‐218T>C, c.‐219C>T, c.‐219delC, c.‐221T>A and c.‐664G>A) detected in the F8 promoter and their correlation with clinical phenotype of the patients. Potential role of these mutations in HA was also assessed. Causality was demonstrated with transient transfection experiments using luciferase reporter gene plasmids and computational analysis. Two molecular changes (c.‐51G>A and c.‐664G>A) did not seem to affect the promoter function of the F8 gene whereas c.‐218T>C, c.‐219C>T, c.‐219delC, c.‐221T>A mutations had an impact on the F8 promoter function and were responsible for HA. Furthermore, these mutations were associated with resistance to 1‐deamino‐8‐d‐argininevasopressin (desmopressin) therapy when they were causative. When molecular variation was detected in F8 promoter, we propose to use prediction software and to verify predictions by reporter gene analysis. If the mutation is causative, it will be probably associated with a lack of therapeutic response to desmopressin and this clinical implication should be considered by clinicians.